Valores hematológicos en Columba Livia (paloma doméstica) de la plaza de Bolívar- Bogotá. (2021)
In the daily clinic, the use of laboratory tests helps to approximate and correlate the physiological variables of the patient, through the interpretation, exploration and daily inquiry that brings us closer to a definitive diagnosis. For forgotten or ignored species, such as pigeons (Columba livia). Through a descriptive research design, the hematological values of the pigeons of the Plaza de Bolívar in Bogotá were determined, captured by the CAP pigeon care center, located at the Antonio Nariño University, Usme headquarters, in which the they collected 1,000. stories. . clinics of which 227 birds applied the inclusion criterion that specifies that all those birds that in their clinical history did not have disease reports were taken